IDDF2018-ABS-0079 The safety of percutaneous radiofrequency ablation with cool-tip electrode for the treatment of hepatocellular carcinoma. (June 2018) - Thi Thu Huyen, Nguyen; Bang, Mai Hong; Riep, Tran Van; Thinh, Nguyen Tien
Abstract : Background: Although ablation therapy has been accepted as a safe technique for treatment of unrespectable HCCs, investigation of its complications has been limited, and A physician who performs ablation treatment should be aware of the broad spectrum of complications. We aim to study the safety of percutaneous Radiofrequency Ablation with Cool-tip for the treatment of HCC. Methods: A prospective study involved 82 cirrhotic HCC patients (mean tumour size: 31, 54±10, 7 mm) underwent percutaneous RFA using Cool-tip RF electrode (COOL-TIP E SERRIES, COVIDIEN) at the 108 hospital, from September 2012 to October 2016). Patients were evaluated during RFA treatment, throughout the immediate post RFA course, and then every 3 months after RFA to assess for the development of treatment-related complications. Results: A total 115 procedures were performed successfully. No death related to the technique. There were 3 cases with early complication (1 diaphragm perforation, 1 lesion abcess, 1 pleural effusion, ) and tumour seeding developed in 2 patients. The rate of Post RFA syndrome was 67%, but most of the symptoms were transient and self-limited. Conclusions: RFA using Cool-tip is a safe treatment for patients HCC.